The Anthropocene The Human Era and How It Shapes Our Planet. - Schwägerl, Christian (Synergetic Press, 2018)
In this book, Schwägerl explores the ways in which our relationship with nature has gone awry, and taking a step further than this, he suggests how humanity can take action to create a more fruitful future for ourselves and our planet.